Anatomical Correlates of Non-Verbal Perception in Dementia Patients - Lin, Pin-Hsuan; Chen, Hsiu-Hui; Chen, Nai-Ching; Chang, Wen-Neng; Huang, Chi-Wei; Chang, Ya-Ting; Hsu, Shih-Wei; Hsu, Che-Wei; Chang, Chiung-Chih (Frontiers in Aging Neuroscience, 2016)
Purpose: Patients with dementia who have dissociations in verbal and non-verbal sound processing may offer insights into the anatomic basis for highly related auditory modes. Methods: To determine the neuronal networks on non-verbal perception, 16 patients with Alzheimer’s dementia (AD), 15 with behavior variant fronto-temporal dementia (bv-FTD), 14 with semantic dementia (SD) were evaluated and compared with 15 age-matched controls. Neuropsychological and auditory perceptive tasks were included to test the ability to compare pitch changes, scale-violated melody and for naming and associating with environmental sound. The brain 3D T1 images were acquired and voxel-based morphometry (VBM) was used to compare and correlated the volumetric measures with task scores. Results: The SD group scored the lowest among 3 groups in pitch or scale-violated melody tasks. In the environmental sound test, the SD group also showed impairment in naming and also in associating sound with pictures. The AD and bv-FTD groups, compared with the controls, showed no differences in all tests. VBM with task score correlation showed that atrophy in the right supra-marginal and superior temporal gyri was strongly related to deficits in detecting violated scales, while atrophy in the bilateral anterior temporal poles and left medial temporal structures was related to deficits in environmental sound recognition. Conclusions: Auditory perception of pitch, scale-violated melody or environmental sound reflects anatomical degeneration in dementia patients and the processing of non-verbal sounds is mediated by distinct neural circuits.